Experimental and numerical study on scratch performance of additively manufactured continuous carbon fibre reinforced polyamide 6 composites. (10th November 2022) - Man, Ziyan; Wan, Boyang; Wang, Hongjian; Li, Qing; Chang, Li
Abstract: In the present work, scratch tests were conducted to study the surface deformation behaviour of additively manufactured continuous carbon fibre (CF) reinforced polyamide 6 (PA6) composites. The effect of fibre orientation was investigated by considering three scratch directions, i.e. normal, transverse, and longitudinal to the fibres. Different scratch deformation modes were identified, namely mild abrasion, fibre breakage and fibre removal, depending on the normal load. The critical loads for the transitions between various deformation modes were greatly affected by fibre orientations. In particular, with the increase of load, samples with fibres in normal direction were more likely to experience fibre breakage and removal than the other two, associated with higher friction and wear rate. To further understand the failure behaviour of fibres, a finite element model was established to analyse the stresses generated in the contact region, especially on fibres. Special emphasis was focused on fibre/matrix interfacial bonding and fibre distribution, as the two main parameters concerned for the fused filament fabrication (FFF) technique. It was found that the interfacial bonding plays a key role in determining the failure process of fibre, as well as the size and shape of the formed fibre debris. The work contributes to an in-depth understanding of the scratch and tribological performance of carbon fibre reinforced polymers (CFRPs), thereby providing useful guidelines for the design and selection of CFRPs using additive manufacturing (AM) technology. Graphical abstract: Image 1